A retrospective analysis of early experience with modified complete primary repair of exstrophy bladder (CPRE) in neonates and children - Kurbet, Santosh B. (Medknow Publication & Media Pvt Ltd, 2013)
OBJECTIVE: To study the problems faced during the surgery and follow-up of modified complete primary repair of exstrophy (CPRE) technique. Initial experience with CPRE and its short- and long-term outcomes with respect to continence status and psychosocial impact are reported. MATERIALS AND METHODS: A retrospective review of the hospital case records from March 2008 to September 2012 was performed. Data of patients with bladder exstrophy managed by a single paediatric surgeon using modified CPRE technique were analysed. Quality of life and psychosocial impact of the surgery were assessed using Pediatric Quality of Life Inventory (PedsQL 4.0) and compared with those of typical peers. RESULTS: Eight children (age 4 days-12 years) underwent CPRE using modified Mitchell's technique. Two patients (25%) experienced early postoperative complications, with infection and fistula developing in one each. All the patients were doing well on follow-up, with variable continence rates and good cosmesis. Mean duration of follow-up was 18.5 months (range 6 months-4 years). Five out of seven (71%) children were continent or partially continent. One case was lost to follow-up. PedsQL scores were comparable with those of age-matched peers in all domains except the social functioning domain in 8-12 years age group (83.53 ± 9.70 vs. 77.86 ± 10.22, P < 0.05). CONCLUSION: Our preliminary results with modified CPRE in neonates and children have been encouraging. No major complications were observed. Continence rate was satisfactory and cosmetic results were good. Though the technique is being practiced at several Indian centres, there is a paucity of comprehensive Indian data on CPRE.